2017
DOI: 10.1152/jn.00895.2016
|View full text |Cite
|
Sign up to set email alerts
|

Models of utricular bouton afferents: role of afferent-hair cell connectivity in determining spike train regularity

Abstract: Vestibular bouton afferent terminals in turtle utricle can be categorized into four types depending on their location and terminal arbor structure: lateral extrastriolar (LES), striolar, juxtastriolar, and medial extrastriolar (MES). The terminal arbors of these afferents differ in surface area, total length, collecting area, number of boutons, number of bouton contacts per hair cell, and axon diameter (Huwe JA, Logan CJ, Williams B, Rowe MH, Peterson EH. 113: 2420-2433, 2015). To understand how differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Most afferents have 'dimorphic' terminals and receive inputs from both type I and type II hair cells [1]. Irregular dimorphic afferents have fewer bouton terminals than regular dimorphic afferents [4,5], suggesting that the ratio of calyx-to-bouton terminals affects afferent properties. Note that some of the input to dimorphic afferents could come from type II hair cells by direct synapses on the outer surface of calyces [3,77].…”
Section: Efferent Inputs Can Affect the Response Properties Of Dimorpmentioning
confidence: 99%
See 2 more Smart Citations
“…Most afferents have 'dimorphic' terminals and receive inputs from both type I and type II hair cells [1]. Irregular dimorphic afferents have fewer bouton terminals than regular dimorphic afferents [4,5], suggesting that the ratio of calyx-to-bouton terminals affects afferent properties. Note that some of the input to dimorphic afferents could come from type II hair cells by direct synapses on the outer surface of calyces [3,77].…”
Section: Efferent Inputs Can Affect the Response Properties Of Dimorpmentioning
confidence: 99%
“…In the present study, we only recorded from calyces in the central regions of the cristae and cannot speculate about the effects on calyces that innervate the peripheral regions. Afferents that innervate the central region have the most irregular resting discharge [1], receive inputs only from calyx terminals or have fewer bouton terminals compared to peripheral regular dimorphic afferents [4,5], show the largest efferent-mediated effects [11][12][13]54], and have an abundance of KCNQ channels [31].…”
Section: Efferent Inputs Can Affect the Response Properties Of Dimorpmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the net effect of efferents on Type II hair cells/bouton terminals is small, efferent-mediated changes in dimorphic fibers are likely to be dominated by calyx terminals. It has been shown that irregular dimorphic afferents have fewer bouton terminals than regular dimorphic afferents (Goldberg et al, 1990a;Holmes et al, 2017) and are therefore expected to show more robust responses to efferent inputs than regular dimorphic afferents. This is consistent with the inhibition of afferents as a function of CV* observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ion channels, models have shown that the size and rate of synaptic events also shapes spike-timing statistics. For example, turtle vestibular neurons having small compact terminal arbors with bouton synapses on few hair cells might produce large and temporally brief synaptic events whereas neurons with extended arbors containing hundreds of bouton-like terminals on many spatially dispersed hair cells may produce small but rapidly arriving events (Goldberg and Holt, 2013;Holmes et al, 2017). A sustained-A model can produce remarkably regular firing patterns when stimulated by a steady depolarization, such as that provided by a step of current (Fig.…”
Section: A Developmental Convergence In Vgn Firing Patternsmentioning
confidence: 99%